Minimally invasive surgery in neonates and infants - Lin Tiffany; Pimpalwar Ashwin (Wolters Kluwer Medknow Publications, 2010)
Minimally invasive surgery (MIS) has significantly improved the field of surgery, with benefits including shorter operating time, improved recovery time, minimizing stress and pain due to smaller incisions, and even improving mortality. MIS procedures, including their indications, impact, limitations, and possible future evolution in neonates and infants, are discussed in this article.